The Level of Support For Successful Learning in Inclusive Primary School in Banjarmasin - Amka, Amka; Kusumastuti, Dewi Ekasari (Journal of ICSAR, 2019)
The purpose of this study is to provide an overview of the level of support for successful learning in Inclusive Primary Schools in Banjarmasin. It reviewed three aspects of success support, namely: institutional aspects, teacher aspects, and aspects of facilities and infrastructure. These three aspects are very essential to support the success of inclusion learning that researchers believe makes a strong contribution. The approach in this study was a quantitative approach with survey research. The data sources in this study were 10 inclusive primary school principals in the city of Banjarmasin and secondary data sources were documentation, photos, records of results of activities and letters. Data collection techniques in this study were observation and documentation. The data were analyzed using descriptive statistical analysis. This research was conducted by selecting 10 samples of Inclusive Primary Schools in Banjarmasin City. The results indicate that the level of support for successful learning in Banjarmasin Inclusive Primary School in terms of teacher aspects is 44%, 46% for institutional aspects, and 10% for facilities and infrastructure aspects. This means that the level of support for teacher aspects and institutional aspects is included in the category of moderate support, while the level of support for infrastructure and facilities is included in the category of very low